Determinants of FDI in BRICS countries: A panel analysis - Narayanamurthy Vijayakumar; Perumal Sridharan; Kode Chandra Sekhara Rao (International Journal of Business Science & Applied Management (IJBSAM), 2010)
This study examines the factors determining FDI inflows of BRICS countries using annual dataset from the period 1975 to 2007 (for Russia required data set is available from 1990 onwards). The study employs Panel data analysis and finds that the selected variables Market size, Labour cost, Infrastructure, Currency value and Gross Capital formation as the potential determinants of FDI inflows of BRICS countries. The Economic Stability and Growth prospects (measured by inflation rate and Industrial production respectively), Trade openness (measured by the ratio of total trade to GDP) are seems to be the insignificant determinant of FDI inflows of the BRICS countries. The empirical results are robust in general for alternative variables determining FDI flows.
Keywords: 650; foreign direct investment; panel data; economic stability